NON-COMMUNICABLE DISEASES - RISK FACTORS SURVEILLANCE AMONG ADULT POPULATION IN THENI DISTRICT, SOUTHERN TAMIL NADU (Asian Journal of Medical Research and Health Sciences, 2026)
Context: Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide, with India contributing a significant share of the global burden. The early onset and poor control of NCDs in rural populations highlight the need for comprehensive risk factor assessment. Aims & Objectives: This study aimed to determine the prevalence of behavioural, physical, and biochemical risk factors among adults with NCDs and find out their association with metabolic control. Materials & Methods: A cross-sectional analytical study was conducted from September 2023 to February 2024 at a tertiary care hospital in Theni, Tamil Nadu. Using systematic random sampling, 402 adults (≥18 years) attending the NCD outpatient clinic were enrolled. Data were collected employing the WHO STEPS approach, encompassing behavioural, physical, and biochemical parameters. Statistical analyses were performed using Epi-Info; categorical variables were tested using the Chi-square test, and P